Experimental investigation on the development of pore clogging in novel porous pavement based on polyurethane. (20th October 2020) - Xu, Shifa; Lu, Guoyang; Hong, Bin; Jiang, Xinyan; Peng, Geng; Wang, Dawei; Oeser, Markus
Highlights: A new permeable pavement material is developed by replacing bitumen with novel Polyurethane (PU) binder. The clogging effect was firstly simulated by a real tire polishing machine. The simulation is closer to the actual state. The clogging characteristics of different PU bound pervious mixtures are examined and compared with conventional porous asphalt (PA). The XCT scanning was selected to investigate the clogging depth and the distribution of clogging agent within the porous pavement material. Abstract: Permeable pavements are often affected by pore clogging, which leads to their functional failure and reduced service life. However, the clogging mechanism and its impact on the permeability and complex pore microstructures in pervious pavement remains unclear. The aim of current study is to quantify the clogging behavior in pervious pavement materials (PPMs) and carry out investigations on the development of pore characteristics and permeability. Novel Polyurethane bound Pervious Mixture (PUPM) were adopted for comparative study in present research with conventional Porous Asphalt (PA). The Aachen Polishing Machine (APM) was selected to perfectly serve as a simulator for clogging process of pavement in the actual service condition. The permeability and pore microstructure of the pervious pavement material was then characterized by using the self-developed permeameter and X-ray Computed Tomography (CT) scanning respectively. The development of pore characteristics in terms of clogging was experimentally illustrated. The developed experiments and analysis can further strengthen the understanding of the clogging mechanism within the porous pavement material. The results can also serve for the optimization of the pervious pavement design in the engineering application.